Pre-injury administration of morphine prevents development of neuropathic hyperalgesia through activation of descending monoaminergic mechanisms in the spinal cord in mice - Rashid Md Harunor; Ueda Hiroshi (SAGE Publishing, 2005)
Abstract The present study examined whether pre-injury administration of morphine can prevent partial sciatic nerve injury-induced neuropathic pain in mice. We observed that pre-injury administration of subcutaneous (s.c.) and intracerebroventricular (i.c.v.) morphine dose-dependently prevented the development of both thermal and mechanical hyperalgesia at 7 days following nerve injury in mice. The pre-injury morphine (s.c.)-induced analgesia was significantly blocked by pretreatment with naloxone injected s.c. or i.c.v., but not i.t., suggesting that systemic morphine produced the pre-emptying effects mainly by acting at the supra-spinal sites. Since it is believed that activation of descending monoaminergic mechanisms in spinal cord largely contributes to the supra-spinal analgesic effects of morphine, we investigated the involvement of serotonergic and noradrenergic mechanisms in spinal cord in the pre-injury morphine-induced analgesic effects. We found that pre-injury s.c. morphine-induced analgesic effect was significantly blocked by i.t. pretreatment with serotonergic antagonist, methysergide and noradrenergic antagonist, phentolamine. In addition, pre-injury i.t. injection of serotonin uptake inhibitor, fluoxetine and α2-adrenergic agonist, clonidine significantly prevented the neuropathic hyperalgesia. We next examined whether pre-injury morphine prevented the expression of neuronal hyperactivity markers such as c-Fos and protein kinase C γ (PKCγ) in the spinal dorsal horn. We found that pre-injury administration of s.c. morphine prevented increased expressions of both c-Fos and PKCγ observed following nerve injury. Similar results were obtained with i.t. fluoxetine and clonidine. Altogether these results suggest that pre-injury administration of morphine might prevent the development of neuropathic pain through activation of descending monoaminergic pain inhibitory pathways.